2007
DOI: 10.1126/science.1146421
|View full text |Cite
|
Sign up to set email alerts
|

Epoxide-Opening Cascades Promoted by Water

Abstract: Selectivity rules in organic chemistry have been inferred largely from nonaqueous environments. In contrast, enzymes operate in water, and the chemical effect of the medium change remains only partially understood. Structural characterization of the "ladder" polyether marine natural products raised a puzzle that persisted for 20 years: Although the stereochemistry of adjacent tetrahydropyran (THP) cycles would seem to arise from a biosynthetic cascade of epoxide-opening reactions, experience in organic solvent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
178
1
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 267 publications
(190 citation statements)
references
References 33 publications
2
178
1
4
Order By: Relevance
“…These exceedingly complex PKs contained one to three glycosylation sites. Even though 43A-B are presumably enzymatically cyclized, very recent experiments addressed a long-standing problem concerning the biosynthesis of such polyether ladders [421]. The solvent water was found to be critical in guiding ring size selectivity for the tandem epoxide ring openings initiated from a single tetrahydropyran template.…”
Section: Marine Fatty Acids Andmentioning
confidence: 99%
“…These exceedingly complex PKs contained one to three glycosylation sites. Even though 43A-B are presumably enzymatically cyclized, very recent experiments addressed a long-standing problem concerning the biosynthesis of such polyether ladders [421]. The solvent water was found to be critical in guiding ring size selectivity for the tandem epoxide ring openings initiated from a single tetrahydropyran template.…”
Section: Marine Fatty Acids Andmentioning
confidence: 99%
“…It is clear from the data in Table 1 that selectivity in the cyclization reactions under neutral aqueous conditions is very sensitive to the identity of the template and the size of the ring being formed (10)(11)(12). We were particularly surprised to find that a 1:1 mixture of products resulted from the seemingly minor change from 1a to 1b, which differ only by the replacement of an oxygen atom with a CH 2 group in the template (entries 1 and 2).…”
Section: Resultsmentioning
confidence: 79%
“…Up to this point, the importance of the template structure for selective endo cyclizations has been emphasized, yet as noted above, water was also implicated (10). Further investigation has revealed that selectivity is much less sensitive to the identity of the solvent than is the reaction rate (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a palladium-catalyzed tandem reaction resulted in multirings in one step (Scheme 12) (48). Another example is Jamison's synthesis of the core piece of ''ladder'' polyether marine natural products through a biomimetic cascade cyclization in neutral water (Scheme 13) (49).…”
Section: Synthesis Without Protectionsmentioning
confidence: 99%